2018
DOI: 10.1177/0271678x18771440
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the pharmacological agents that have been tested against spreading depolarizations

Abstract: Spreading depolarization (SD) occurs alongside brain injuries and it can lead to neuronal damage. Therefore, pharmacological modulation of SD can constitute a therapeutic approach to reduce its detrimental effects and to improve the clinical outcome of patients. The major objective of this article was to produce a systematic review of all the drugs that have been tested against SD. Of the substances that have been examined, most have been shown to modulate certain SD characteristics. Only a few have succeeded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 256 publications
(485 reference statements)
1
31
0
Order By: Relevance
“…Notably, anesthetics can induce in vivo slow rhythmic activity, including cortical UP/DOWN states, and some of them can inhibit CSD, although there are controversial reports about their effect on CSD (Klass et al, 2018). Similar to cholinergic modulations, anesthetics show complex mechanisms and some of them can reduce neuronal network excitability in the neocortex (Becker et al, 2012;Voss et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, anesthetics can induce in vivo slow rhythmic activity, including cortical UP/DOWN states, and some of them can inhibit CSD, although there are controversial reports about their effect on CSD (Klass et al, 2018). Similar to cholinergic modulations, anesthetics show complex mechanisms and some of them can reduce neuronal network excitability in the neocortex (Becker et al, 2012;Voss et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, we observed that this can lead to self-limited abortive CSD. These are synergic effects that could be used in migraine therapy for inhibiting CSD and its consequences, and possibly in other pathological conditions in which spreading depolarizations are involved (Klass et al, 2018). Several drugs are used for migraine therapy in clinical practice, with different mechanisms that include decreased excitability of cortical circuits, modulation of neuronal plasticity, reduction of circulating levels of calcitonin generelated peptide (CGRP, a peptide released by nociceptors and implicated in migraine headache) and/or inhibition of cortical spreading depression (Ayata et al, 2006;Costa et al, 2013;Mantegazza et al, 2010;Sprenger et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cerebral edema is a key prognosticator of unfavorable outcome in acute ischemic, hemorrhagic or traumatic brain injury, in which spreading depolarizations (SDs) are implicated. Moreover, the robust correlate of lesion progression after acute brain injury is a characteristic pattern of SDs, which serves as an electrophysiological biomarker of injury progression, and is considered as a target of pharmacological intervention (Lauritzen et al, 2011Klass et al, 2018). SD is a slowly propagating wave (2-6 mm/min) of a near complete cellular depolarization followed by the transient depression of neural activity and cytotoxic edema (Somjen 2001, Dreier 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Although SD can be modulated by different drugs in intact tissue, for example, by NMDA receptor antagonists, SD waves are generally pharmacoresistant in metabolically compromised tissue, a fact likely ascribed to the lack of deep knowledge of the mechanical aspects of the initiation and propagation of SD in the ischemic brain. Although NMDA antagonists, such as ketamine or MK-801, might attenuate SD in animals after brain injury [81], only few clinical cases have reported that antagonizing NMDA receptors might prevent SD in patients [82]. The fact that targeting excitotoxicity through NMDA receptors antagonists does not result in clear benefits in stroke patients brings even more controversy as to whether NMDA receptors are adequate targets for abolishing SD and attenuating secondary damage.…”
Section: Spreading Depolarizationmentioning
confidence: 99%